2018
DOI: 10.1590/0366-69132018643712325
|View full text |Cite
|
Sign up to set email alerts
|

On mechanical properties and bioactivity of PVDF-BCP composites

Abstract: A ceramic/polymer biocomposite with high potential for multifunctional practical applications in bone tissue engineering was synthesized by using a well-known piezoelectric polymer, polyvinylidene fluoride (PVDF), and a high bioactive biphasic calcium phosphate (BCP) ceramic obtained from recycled fish bones. High-bioactivity was observed for the PVDF-BCP composite when it was subjected to conditions that simulate the animal body once a very thick apatite layer (9 μm) was grown on its surface in an immersion e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Zhang et al sintered fish bones in a furnace at three different temperatures of 700, 800, and 900 °C, respectively (heating rate of 5 °C/min), in air for 1 h. This study confirmed the β-TCP content in fish bones calcined at 900 °C and revealed the mechanism of changing the composition ratio of BCP by heating [32]. The same calcination temperature of 900 After a literature survey on the methods applied to produce BCP powders from fish discards, one can conclude that the most common method used for the extraction of these materials is thermal calcination [102][103][104][105] even if other methods, such as hydrothermal transformation [106], aqueous precipitation [92], laser irradiation [90], alkaline [84,107], and enzymatic hydrolysis [108], can be used as well.…”
Section: From Fish Discards To Powder Preparationsupporting
confidence: 66%
See 3 more Smart Citations
“…Zhang et al sintered fish bones in a furnace at three different temperatures of 700, 800, and 900 °C, respectively (heating rate of 5 °C/min), in air for 1 h. This study confirmed the β-TCP content in fish bones calcined at 900 °C and revealed the mechanism of changing the composition ratio of BCP by heating [32]. The same calcination temperature of 900 After a literature survey on the methods applied to produce BCP powders from fish discards, one can conclude that the most common method used for the extraction of these materials is thermal calcination [102][103][104][105] even if other methods, such as hydrothermal transformation [106], aqueous precipitation [92], laser irradiation [90], alkaline [84,107], and enzymatic hydrolysis [108], can be used as well.…”
Section: From Fish Discards To Powder Preparationsupporting
confidence: 66%
“…These synthesis techniques can be generally classified into four categories, as follows: dry methods, wet chemical synthesis, high-temperature processing, and synthesis from biogenic resources (Figure 2) [101]. After a literature survey on the methods applied to produce BCP powders from fish discards, one can conclude that the most common method used for the extraction of these materials is thermal calcination [102][103][104][105] even if other methods, such as hydrothermal transformation [106], aqueous precipitation [92], laser irradiation [90], alkaline [84,107], and enzymatic hydrolysis [108], can be used as well.…”
Section: From Fish Discards To Powder Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of energy costs, environmental concerns and with the dangers associated with the use of asbestos, manmade vitreous fibers (MMVF) such as refractory ceramic fibers (RCF) and alkaline earth silicate (AES) wools have been used. Reasons for their employment are directly linked to their low density, low thermal conductivity, low shrinkage, high resilience and high thermal shock resistance [1,2]. These characteristics allow their use as wear linings in a great variety of equipment such as tempering and reheating furnaces and steel ladle covers.…”
Section: Introductionmentioning
confidence: 99%